Orientación tributaria a la comunidad como evaluación colaborativa en un curso tributario - Castillo Dextre, Cielo Bertha (2023)
The Accounting Taxation 1 course, from to the seventh level of the Accounting Sciences Faculty, contains tax concepts applied to career, linked to both citizens and the business world. Regarding the evaluation system, it involves both individual and collaborative evaluations, which include tax orientation towards the citizen, an innovative ingredient to the course, and promotes tax awareness with a focus on University Social Responsibility. This paper shows an experience where students, formed in work teams, conducted tax orientation to individuals and small businesses in the PUCP community. In the first semester of 2022, the queries and answers were performed under a virtual environment, using the social networks of «Fomentando conciencia tributaria – FCT» (the faculty student group) for the capture of queries. Google tools and the Zoom platform were used for coordination meetings between the teams, the teacher and FCT members. On the second semester of 2022, with the return to the classrooms at PUCP, requests and answers were held directly in personal way at an internal event on campus organized by the Federation of Students of the PUCP (FEPUCP), called «Feria del pollito» (Chick Fair), whose exhibitors were small businesspeople from the PUCP community.